Crystal structures of three 6-substituted coumarin-3-carboxamide derivatives - Gomes, Lígia R. (2016)
Three coumarin derivatives, viz. 6-methyl-N-(3-methyl-phen-yl)-2-oxo-2H-chromene-3-carboxamide, C18H15NO3 (1), N-(3-meth-oxy-phen-yl)-6-methyl-2-oxo-2H-chromene-3-carboxamide, C18H15NO4 (2), and 6-meth-oxy-N-(3-meth-oxy-phen-yl)-2-oxo-2H-chromene-3-carboxamide, C18H15NO5 (3), were synthesized and structurally characterized. The mol-ecules display intra-molecular N-H⋯O and weak C-H⋯O hydrogen bonds, which probably contribute to the approximate planarity of the mol-ecules. The supra-molecular structures feature C-H⋯O hydrogen bonds and π-π inter-actions, as confirmed by Hirshfeld surface analyses.